The TRIANGLE operation: radical surgery after neoadjuvant treatment for advanced pancreatic cancer$da single arm observational study - Hackert, Thilo; Strobel, Oliver; Michalski, Christoph; Mihaljevic, André Leopold; Mehrabi, Arianeb; Müller, Beat P.; Berchtold, Christoph; Ulrich, Alexis; Büchler, Markus W. (HPB, 2017)
BACKGROUND: Neoadjuvant therapy is an important strategy for locally advanced pancreatic cancer (PDAC) as resection rates increase with modern chemotherapy regimens even in patients with arterial tumor encasement. The aim of this study is the description of technique and initial outcomes of a new type of radical and arterial-sparing resection after neoadjuvant treatment for locally advanced PDAC. METHODS: The surgical technique and perioperative results of a new type of operation are described, comprising radical tumor removal by sharp dissection along the celiac axis and the superior mesenteric artery with complete dissection of all soft tissue between both - arteries and superior mesenteric/portal vein (TRIANGLE operation). RESULTS: 15 patients underwent artery-preserving tumor removal without mortality, 7/15 patients showed postoperative complications and an R0 resection was achieved in 6/15 patients. Functional outcome was good in 11/15 patients despite the extended approach of dissection. CONCLUSION: After neoadjuvant therapy for locally advanced PDAC, surgical exploration should be attempted in patients with stable disease or remission to clarify true vascular infiltration. In case of absent viable tumor, the described technique allows to perform radical surgery without arterial resection in this subgroup of patients.